2020
DOI: 10.1002/jcp.29428
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2‐dependent H3K27me3 modification dynamically regulates vitamin D3‐dependent epigenetic control of CYP24A1 gene expression in osteoblastic cells

Abstract: Epigenetic control is critical for the regulation of gene transcription in mammalian cells. Among the most important epigenetic mechanisms are those associated with posttranslational modifications of chromosomal histone proteins, which modulate chromatin structure and increased accessibility of promoter regulatory elements for competency to support transcription. A critical histone mark is trimethylation of histone H3 at lysine residue 27 (H3K27me3), which is mediated by Ezh2, the catalytic subunit of the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The first step in the degradation cascade of 1α,25-OH 2 D 3 is hydroxylation at the C-24 position by 24-hydroxylase (CYP24A1) [ 137 ]. CYP24A1 is expressed in all vitamin D target cells, and its expression is very rapidly and strongly increased after 1α,25-OH 2 D 3 binding to VDRs [ 138 , 139 , 140 , 141 ]. The VDR level is tightly linked to the induction of CYP24A1 expression and 24-hydroxylase activity and, consequently, degradation of 1α,25-OH 2 D 3 .…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…The first step in the degradation cascade of 1α,25-OH 2 D 3 is hydroxylation at the C-24 position by 24-hydroxylase (CYP24A1) [ 137 ]. CYP24A1 is expressed in all vitamin D target cells, and its expression is very rapidly and strongly increased after 1α,25-OH 2 D 3 binding to VDRs [ 138 , 139 , 140 , 141 ]. The VDR level is tightly linked to the induction of CYP24A1 expression and 24-hydroxylase activity and, consequently, degradation of 1α,25-OH 2 D 3 .…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…1, 25(OH) 2 D 3 treatment affects histone modification levels in NLRP3 and Nrf2 promoters in DOX-induced cardiomyopathy. Previous studies have reported that 1,25(OH) 2 D 3 can affect histone modifications to regulate downstream target gene expression and impact transcriptional regulation (37). To clarify the effect of 1,25(OH) 2 D 3 on the level of histone modification in the NLRP3 promoter, ChIP assay was used to assess the levels of H3K4 (H3K4me 3 ) and H3K27 (H3K27me 3 ) trimethylation, in addition to H2AK119 monoubiquitination (H2AK119Ub), in the NLRP3 promoter region.…”
Section: 25(oh) 2 D 3 Inhibits the Activation Of A Pro-fibrotic And I...mentioning
confidence: 99%
“…Chromatin organization is dynamically altered by histone post-translational modifications (PTMs) that mediate epigenetic regulation of osteogenic lineage differentiation and osteoblast maturation ( van Wijnen and Westendorf, 2019 ). We and others have identified multiple enzymes expressed in osteogenic cells that mediate or recognize lysine methylation ( Dashti et al, 2023 ; Dudakovic et al, 2016 ; Dudakovic et al, 2020 ; Galvan et al, 2021 ; Khani et al, 2017 ; Moena et al, 2020a ; Rojas et al, 2019 ; van Wijnen et al, 2021 ), demethylation ( Dudakovic et al, 2017 ; Rojas et al, 2015 ; Rummukainen et al, 2022 ) or acetylation of histones ( Dudakovic et al, 2013 ; Galea et al, 2020 ; Paradise et al, 2020 ; Paradise et al, 2022 ; Shen et al, 2003 ; Sierra et al, 2003 ), as well as DNA methylation and hydroxylation ( Thaler et al, 2022 ). These epigenetic regulatory enzymes can induce modifications on different amino acids located on histone tails including lysines (K), arginines (R), and serines (S) ( Tan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%